Common walnut (Juglans regia L.) wood characteristics in two Italian plantations - Castro, Gaetano; Bergante, Sara; Sansone, Dalila; Bidini, Caludio; Pelleri, Francesco (Annals of Silvicultural Research, 2019)
The Woodnat project (H2020) has the goal of identifying the problems that led to poor yields in walnut plantations established under the financial support of EU 2080/92 Regulation and Rural Development Programme, and of improving the market demand for smaller assortments. Some of the plantations monitored in the framework of the project needed thinning: one, an experimental stand with 5 plots with different layouts and species established in 1994, was thinned in spring 2018; in a second one, a polycyclic plantation established in 1996 with common walnut, hybrid poplar and nurse trees, the walnut was thinned in spring 2017. At thinning, sample disks were taken at the base of 5 trees randomly selected at each site for the determination of density and shrinkage in the radial, tangential and longitudinal direction. The average density was 0.52g/cm3; the average tangential shrinkage was 12%, while the average radial shrinkage was 6.7%. There were differences in behaviour between the samples from the two sites, probably due to different vegetal materials, age of the plantations and cultivation models.